Dandyism and transcultural modernity : the dandy, the flaneur, and the translator in 1930s Shanghai, Tokyo, and Paris /: the dandy, the flaneur, and the translator in 1930s Shanghai, Tokyo, and Paris. (2014) - Peng, Xiaoyan, 1952-
No abstract available